Божевільний. юродивий, блазень як модус співіснування митця і суспільства у літературі 20-х - початку 30-х років XX сторіччя (на прикладі драматургії Миколи Куліша) - Гай, Є. (Літературознавчі обрії. Праці молодих учених, 2010)
The author researches the images of madman, «God’s fool» and jester in such dramas by Mykola Kulish as «Narodnyy Malakhyi», «Patetychna Sonata» and «Maklena Hrasa». These images reflect a way of coexistence of an artist and society in the literature of the 20’s – the beginning of the 30’s of the XX century. They are closely related to the images of flute and pipe which are also analyzed in the article. In order to study the problem in question and trace the presenting peculiarities of the mentioned above images and motives the author also applies Ukrainian and Russian context and works by such writers as Khvylovy, Tychyna, Bulhakov, Olesha and Erdman.